Perlindungan Hak Tanah untuk Keberlanjutan Agribisnis: Peran Pendaftaran Tanah dalam Mengamankan Aset Pertanian - Adi Rahmanto; Aprila Niravita; Muhammad Adymas Hikal Fikri; Harry Nugroho (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
The sustainability of the agribusiness sector is very dependent on the certainty of land rights, which is the main asset for business actors in this sector. Land registration is an important instrument in providing legal certainty for land ownership, which can ultimately encourage stable and sustainable agribusiness development. This article discusses the role of land registration in protecting ownership rights for agribusiness actors in Indonesia and analyzes the role of government policies, such as the Complete Systematic Land Registration Program (PTSL), in speeding up the land certification process. With legal certainty obtained through land certificates, agribusiness actors can avoid agrarian conflicts, gain access to financing, and run businesses more safely and in a planned manner. Apart from that, land registration policies also have the potential to support regional economic development, reduce agrarian conflicts, and encourage sustainable management of land resources. However, implementing this policy still faces challenges, including bureaucratic obstacles and low public understanding. Therefore, the government's role in improving policies and overcoming existing obstacles is very necessary to create an inclusive, competitive and sustainable agribusiness sector in Indonesia.